Assessing Waste Potential and Greenhouse Gas Emissions from Existing Waste Management Systems: A Case Study of Palembang City South Sumatera of Indonesia - Heri Setiawan; Ferdinandus Bangun; Dominikus Budiarto; Yohanes Dicka Pratama (Jurnal Improsci, 2025)
Background, Palembang City South Sumatera of Indonesia faces serious waste challenges, generating about 983-1,200 tons daily, 35% plastic and under 10% recycled. Improper disposal drives methane emissions and climate impacts. This study explores low-cost waste-to-energy (WtE) strategies to cut emissions, support a circular economy, and empower communities through sustainable, participatory waste management. Aim, This study analyzes Palembang’s waste generation and GHG emissions to support sustainable and efficient waste management strategies. Methods, This study used mixed methods to assess Palembang’s waste management and emissions, conducted from July-October 2025, data from key stakeholders were analyzed using IPCC Tier 1 Guidelines to compare baseline and intervention scenarios for sustainable community solutions. Results, The analysis revealed that Palembang City South Sumatera of Indonesia generates approximately 1,000 tons of municipal solid waste per day, with organic waste (56%) and plastic waste (24%) as the dominant fractions. Current waste treatment processes, mainly open dumping and limited composting, result in an estimated carbon emission of 420-460 tons CO₂-eq per day. Scenario modeling indicated that implementing a low-cost waste-to-energy (WtE) system and community-based segregation programs could reduce emissions by up to 55%, while generating additional energy potential of 7-9 MWh per day. These findings demonstrate the significant potential of an integrated waste management approach to simultaneously mitigate greenhouse gas emissions and enhance energy recovery in Palembang. Conclusions, Palembang generates 983-1,200 tons of waste daily, mostly food (40.8%) and plastic (20.4%), with 60% sent to Sukawinatan and 40% to Kramasan landfills. Management still relies on open dumping, causing methane emissions of 2,352.9 tons (65,888.2 tons CO₂-eq) valued at about IDR 1.97 trillion. These results underscore the need for integrated, sustainable waste-to-energy (WtE) solutions. Implication, The study guides policymakers in developing low-cost, sustainable waste management through community-based waste-to-energy (WtE) initiatives that reduce emissions and support a circular, resilient city.